Pentahelix in the creative city: the case of fine arts development in South Jakarta, Indonesia - Adiwan Fahlan Aritenang; Frida Nathania (Creativity Studies)
The emergence of the creative economy as a new economic wave in Indonesia has led to implementing of various policies and strategies since 2006. In particular, South Jakarta, Indonesia, has been designated as a creative city focusing on developing the fine arts subsector. The findings reveal that the development of South Jakarta as a creative city for the fine arts has met the minimum prerequisites required for a creative city in Indonesia. The city has emphasized effectiveness, efficiency, and adequacy in developing the fine arts subsector. The study sheds light on the readiness of South Jakarta’s creative city, which heavily relies on the involvement of the local government and creative communities. Overall, this research offers valuable insights into the roles of the local government and creative communities. It also highlights the need to actively involve academics and the media in the city’s creative city development endeavours.